2014
DOI: 10.7314/apjcp.2014.15.4.1791
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Underserved Vietnamese Americans to Obtain Colorectal Cancer Screening: Evaluation of a Culturally Tailored DVD Intervention

Abstract: Background: Colorectal cancer (CRC) is a leading cause of cancer death among Vietnamese Americans, yet screening remains underutilized. We investigated the effectiveness of a culturally tailored DVD intervention in promoting CRC screening among unscreened Vietnamese Americans age 50 and over. Materials and Methods: Using a community-based participatory research approach, we conducted a trial comparing twenty-eight subjects who received a mailed DVD in Vietnamese, with twenty-eight subjects who received a maile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Seven qualitative studies [100-106] and 7 mixed methods [75,76,[107][108][109][110][111] related to eHealth were identified. Qualitative studies primarily targeted black/AAs (n=3) or diverse populations (n=2) and target breast (n=3) and prostate cancer (n=3) patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven qualitative studies [100-106] and 7 mixed methods [75,76,[107][108][109][110][111] related to eHealth were identified. Qualitative studies primarily targeted black/AAs (n=3) or diverse populations (n=2) and target breast (n=3) and prostate cancer (n=3) patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Vietnamese Americans are disproportionately affected by CRC, with rates increasing from 35.6 to 46.3 per 100,000 men and from 30.5 to 34.2 per 100,000 women between 1990-1994 and 2009-2011, according to Surveillance, Epidemiology and End Results (SEER) program [6]. Despite this, CRC screening uptake remained suboptimal in this group [7], with only 33% to 61% [8][9][10] of eligible Vietnamese Americans are up-to-date with CRC screening, which is lower than the 68.8% screening rate in the general US population [11] as well as the 74.4% goal set forth in the Healthy People 2030 initiative [12].…”
Section: Introductionmentioning
confidence: 99%
“…10 Regional studies found that CRC screening rates ranged from 33 to 61% in populations of community-dwelling Vietnamese Americans aged 50 to 79 in California (52%), 11 Washington (52% for men, 61% for women), 12 and Minnesota (33.1%). 13 These rates lag significantly behind the target CRC screening rate of 70.5% set by Healthy People 2020. 14 Among Asian American ethnicities, Vietnamese Americans had higher levels of unemployment (10.6%) and low levels of socioeconomic status in a 2013 report conducted by John Logan and Weiwei Zhang.…”
Section: Introductionmentioning
confidence: 99%
“…15 The previously conducted regional studies also identified low levels of educational attainment, English-speaking proficiency and self-rated health among Vietnamese American participants. 11 - 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation